2005
DOI: 10.1038/modpathol.3800445
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mucins (MUC1, MUC2, MUC3, MUC4, MUC5AC and MUC6) and their prognostic significance in human breast cancer

Abstract: Mucins are a large family of glycoproteins expressed by many epithelial cells and their malignant counterparts. Much interest has been focused on expression of its members in breast cancer because of their potential role as prognostic indicators and their involvement in cancer therapy. We have examined 1447 cases of invasive breast carcinoma with a long-term follow-up, using tissue microarray (TMA) technology and immunohistochemistry to evaluate the expression profiles of several mucins (MUC1, MUC2, MUC3, MUC4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
255
3
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(302 citation statements)
references
References 47 publications
37
255
3
7
Order By: Relevance
“…Evidence suggests that this overexpression was not due to a gene amplification event, but to an as yet unknown mechanism. MUC1 overexpression is associated with poor prognosis in breast (Rakha et al, 2005) and lung adenocarcinoma (Tsutsumida et al, 2004); however, its influence in the prognosis of mesothelioma has not been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence suggests that this overexpression was not due to a gene amplification event, but to an as yet unknown mechanism. MUC1 overexpression is associated with poor prognosis in breast (Rakha et al, 2005) and lung adenocarcinoma (Tsutsumida et al, 2004); however, its influence in the prognosis of mesothelioma has not been reported.…”
Section: Discussionmentioning
confidence: 96%
“…S5 A and B). In addition, tumors exposed to the combination of tamoxifen and STA-1474 showed increased differentiation, as monitored by membranous expression of the epithelial marker MUC1, which is typically lost during malignant progression (32) (Fig. S8).…”
Section: Combination Treatment Inhibits the Emergence Of Resistance Inmentioning
confidence: 99%
“…Mucins are a family of glycoproteins with high molecular weight that have a large number of tandem repeat domains that vary in length. MUC-1 has been found to be expressed abundantly in many epithelial tumors including the majority of breast cancers, 45 and circulating immune complex containing polymorphic epithelial mucin has been detected in breast cancer patients and patients with benign breast tumors. 46,47 An evaluation of the immunogenicity of MUC1, however, identifies a significant potential obstacle in the use of autoantibodies for cancer diagnosis.…”
Section: Autoantibodies In Breast Cancermentioning
confidence: 99%